Pemanfaatan Aplikasi SIG untuk Pembuatan Peta Jaringan Induk Air Bersih dan Saluran Komunal Limbah Fasilitas Kesehatan - Ariyanto, Yunus; Pujiati, Rahayu Sri; Nuraini, Indah (UPT Penerbitan Universitas Jember, 2023)
Background: Health services are required to keep abreast of changes in technology and community needs. To fulfill these demands, service additions, and changes of health facilities are necessary. All of that makes changes to the health services' spatial layout and infrastructure. One of the elements is maps of the main network of clean water and communal sewers in accordance with the latest conditions of health facilities. Method: The map-making activity was carried out at the Jember Lung and Chest Hospital. The method used in making these maps is assistance in data collection and assistance from experts in digitizing maps using Geographic Information System. Results: Two maps are generated. The first map is the Clean Water Network Map, and the second map is the WWTP Communal Map. Conclusion: The implementation of activities went well and smoothly. GIS can be used as a tool for digitizing maps of health institutions. The digital map can be updated along with developments and changes that have occurred.Keywords: GIS, health facility, health service.